Performance-oriented seismic reliability analysis of structural systems - Gu, Xiaoming (2008)
This thesis attempts to address some of the problems in performance-oriented seismic reliability analysis of structural systems. It contains four parts. In the first part, an extensive literature review is performed on related issues. In the second part, probabilistic models defining three main performance levels are studied for both structural and non-structural components. To incorporate both the structural and non-structural criteria into reliability analysis in a coherent manner, a fuzzy-random reliability model is developed as the third part of this study. Finally, a framework for establishing a probabilistic model of the maximum inter-storey drift in a framed structure is proposed for the purposes of design applications and rapid performance assessment.